Keberkesanan kaedah hafazan di pusat tahfiz - Abdullah, Abdul Hafiz; Safar, Ajmain; Mustari, Ismail; Muhammad, Azhar; Ismail , Idris (UTM, 2003)
The al-Quran or Quranic education is a fundamental division of knowledge for muslims. It covers the learning of reading and pronunciation (qiraat), memorization, the study of meanings and legislation and others. In this light, this study focusses in the techniques of memorizing the al-Quran and the effectiveness of the various techniques. Therefore it tries to discover the history and development of the learning of memorization techniques, its regulation, the importance as well as benefits according to the al-Quran and as-Sunnah. The study tries to compare the modern and traditional techniques of memorization used in Malaysia in the perspectives of learning process, infrastructure, location, communication, administration, enrolment, examination and certification as well as recognition for hafiz graduates both from public as well as private tahfiz institution. The effectiveness of the techniques such as the newly memorized (dars jadid), the sustain of memorization (sabiq) and repetition drills (taqrir/muraja‘ah). Data was gathered from tahfiz students and teachers of the most effective technique and factors influencing students memory. It is hoped that results will help to build a module which will promote to the systematic and effective teaching of the tahfiz, both modern and methodical. This will encourage to the production of a quality and competent generation of hafiz and hafizah.